Enculturation of Students Discipline Character Education in the New Normal at Elementary School - Yoni Ernawanto; Yeny Prastiwi; Sutama Sutama; Minsih Minsih (STAI Hubbulwathan Duri, 2022)
There are three purposes of this study, they are describe 1) enculturation of students discipline character education in the new normal before learning 2) enculturation of students discipline character education in the new normal during learning 3) enculturation of students discipline character education in the new normal after learning. There are many studies on character education, but there are still few that discuss character education for student discipline in the new normal. This research uses a qualitative research. The design of this research is ethnographic. This research was conducted in the fourth grade of SD Negeri 1 Wonogiri in 2021/2022 academic year. Sources of data in this study are principals, teachers and students. In this study, the data collection techniques used were observation and interview techniques. In this research, the researcher uses triangulation to test the validity of the data, namely technique triangulation and source triangulation. The results showed that enculturation of students discipline character education in the new normal before learning was carried out by implementing Health protocols, coming to school before 07.00 and praying. Enculturation of students discipline character education in the new normal during learning, namely students focusing on learning materials, group discussions, and questions and answers. Enculturation of students discipline character education in the new normal after learning, namely by making conclusions, following up, and praying at the end of learning. The results of this study are used as a source of input and reflection material for schools about cultivating moral students throught discipline character education in elementary schools and as material for self-evaluation to contribute in an effort to shape the character of discipline in students.